2021
DOI: 10.1038/s41390-020-01273-w
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions and neurodevelopmental outcomes in extremely low gestation neonates enrolled in the PENUT Trial: a randomized clinical trial

Abstract: and for the PENUT Consortium BACKGROUND: Outcomes of extremely low gestational age neonates (ELGANs) may be adversely impacted by packed red blood cell (pRBC) transfusions. We investigated the impact of transfusions on neurodevelopmental outcome in the Preterm Erythropoietin (Epo) Neuroprotection (PENUT) Trial population. METHODS: This is a post hoc analysis of 936 infants 24-0/6 to 27-6/7 weeks' gestation enrolled in the PENUT Trial. Epo 1000 U/kg or placebo was given every 48 h × 6 doses, followed by 400 U/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
16
1
2
Order By: Relevance
“…Although several studies have compared the neurodevelopmental effects of restrictive and liberal transfusion guidelines and shown no difference in outcome, these studies have not compared the outcome of infants with no transfusions compared with those with 1 or more transfusion, or the effects of transfusion volume on outcomes. 28,[37][38][39] There is some suggestion that pRBC transfusions may be associated with worse neurodevelopmental outcomes. 28,40,41 Large studies have evaluated the association between different hematocrit thresholds and outcome but have not evaluated the impact of transfusion volume on neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have compared the neurodevelopmental effects of restrictive and liberal transfusion guidelines and shown no difference in outcome, these studies have not compared the outcome of infants with no transfusions compared with those with 1 or more transfusion, or the effects of transfusion volume on outcomes. 28,[37][38][39] There is some suggestion that pRBC transfusions may be associated with worse neurodevelopmental outcomes. 28,40,41 Large studies have evaluated the association between different hematocrit thresholds and outcome but have not evaluated the impact of transfusion volume on neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…28,[37][38][39] There is some suggestion that pRBC transfusions may be associated with worse neurodevelopmental outcomes. 28,40,41 Large studies have evaluated the association between different hematocrit thresholds and outcome but have not evaluated the impact of transfusion volume on neurodevelopment. [37][38][39]42 Given potential negative effects of pRBC transfusions, including infection, inflammation, 43 transfusion-related necrotizing enterocolitis, 44 and potentially adverse developmental effects, it is ideal to implement strategies to minimize the need for transfusions, including delayed cord clamping, limiting phlebotomy, use of restrictive transfusion guidelines, and ESAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the post hoc analysis of the PENUT trial indicated that each transfusion of RBCs was associated with a decrease in mean cognitive score, motor score, and language score (BSID-III). Moreover, significant negative associations between BSID-III scores, transfusion volume, and donor exposure were observed in the placebo group, but not in the rhEPO group ( 14 ). Since an early start of rhEPO therapy significantly reduced the number of RBC transfusions, as shown in the updated Cochrane Review and in the recent PENUT trial ( 15 , 16 ), rhEPO may still reclaim its value in the patient blood management of very preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…), İVK ve PVL riskini azalttığı; düzeltilmiş yaşı 18-22 aylık bebeklerde nörogelişimsel sonuçların daha iyi olduğu (Bayley II Mental Development Index skorlarının daha iyi olduğu), mortalite üzerine etkisiz ve evre ≥3 ROP riskinde anlamlı bir farklılığın olmadığı bildirilmekte, ancak kıstlı faydaları nedeniyle şu an için EPO kullanımı önerilmemektedir[43].Eritrosit transfüzyonunda, eritrosit süspansiyonunun depo süresinin transfüze edilen bebeklerdeki etkisinin incelendiği son meta analizde; kısa süreli (<7 gün) ya da uzun süreli olan eritrosit süspansiyonlarının yetişkin ve çocuklarda kısa dönemde (<30 gün) mortalite üzerine bir etkisinin olmadığı, yenidoğanlarla ilgili olarak ise yeterli verilerin bulunmadığı bildirilirken[20], ÇDDA'lı 377 bebeğin alındığı bir çalışmada taze (<7 gün) eritrosit süspansiyonu ile standart eritrosit süspansiyonu (2-42 gün) transfüze edilen bebeklerin 3 aylık izleminde; NEK, ROP, BPD, İVK, ölüm ve nozokomiyal enfeksiyon bakımından iki grup arasında anlamlı bir farklılığın olmadığı gösterilmiştir[21], ancak; yüksek volümlü transfüzyonlarda plazma potasyumunda artma, sitrat toksisitesine bağlı hipokalsemi gelişme riskleri bulunabilmektedir[6].Prematüre bebeklerde yaşamın ilk dönemlerinde her bir eritrosit transfüzyonun uzun dönemde; kognitif gecikme, dil ve motor fonksiyonlarda azalma ile ilişkili olduğu, transfüzyon sayısının azaltılması ile bu nörolojik hasarlanma riskinin azalabileceği, dolayısıyla restriktif eritrosit transfüzyon eşik değeri kullanımının uzun dönemde potansiyel olarak daha nöroprotektif gözüktüğü bildirilmektedir[61][62][63][64][65].…”
unclassified